2014
DOI: 10.1186/s13059-014-0433-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of synchronous VHL syndrome tumors reveals contingencies and constraints to tumor evolution

Abstract: BackgroundGenomic analysis of multi-focal renal cell carcinomas from an individual with a germline VHL mutation offers a unique opportunity to study tumor evolution.ResultsWe perform whole exome sequencing on four clear cell renal cell carcinomas removed from both kidneys of a patient with a germline VHL mutation. We report that tumors arising in this context are clonally independent and harbour distinct secondary events exemplified by loss of chromosome 3p, despite an identical genetic background and tissue m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…Two prior studies involving hereditary renal cell carcinoma (RCC) concluded that synchronous or metachronous VHL‐associated tumours are as genetically different from each other as tumours from other unrelated individuals with VHL disease . Fisher et al proposed that the divergent genetic profiles found in RCC are probably contingent on early somatic events, but convergence on the phosphoinositide 3‐kinase–AKT–mammalian target of rapamycin signalling pathway was still a common feature across synchronous primary tumours . It is interesting that we have observed stronger evidence for parallel evolution in synchronous PPGL tumours, not only by the detection of common SCNAs, but also by the similarity in the degree of genome instability between the matched PPGL tumours as compared with other cases.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Two prior studies involving hereditary renal cell carcinoma (RCC) concluded that synchronous or metachronous VHL‐associated tumours are as genetically different from each other as tumours from other unrelated individuals with VHL disease . Fisher et al proposed that the divergent genetic profiles found in RCC are probably contingent on early somatic events, but convergence on the phosphoinositide 3‐kinase–AKT–mammalian target of rapamycin signalling pathway was still a common feature across synchronous primary tumours . It is interesting that we have observed stronger evidence for parallel evolution in synchronous PPGL tumours, not only by the detection of common SCNAs, but also by the similarity in the degree of genome instability between the matched PPGL tumours as compared with other cases.…”
Section: Discussionsupporting
confidence: 47%
“…Few studies have performed genomic profiling of multifocal primary tumours. Two prior studies involving hereditary renal cell carcinoma (RCC) concluded that synchronous or metachronous VHL‐associated tumours are as genetically different from each other as tumours from other unrelated individuals with VHL disease . Fisher et al proposed that the divergent genetic profiles found in RCC are probably contingent on early somatic events, but convergence on the phosphoinositide 3‐kinase–AKT–mammalian target of rapamycin signalling pathway was still a common feature across synchronous primary tumours .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for intratumoural heterogeneity (ITH) in PCC/PGL could also be found in other tumours based on low VAF somatic variants and sub‐copy‐number loss detected by SNP‐array analysis in some cases indicating the presence of sub‐clones within tumours (Supplementary Figure 9). Although mutation burden and the general degree of ITH in PCC is lower than in other more aggressive tumour types, ITH in PCC appears to be higher than recently described in familial renal cell carcinomas . Multi‐region type analysis of additional PCC tumours will be required to validate and generalize our findings.…”
Section: Discussionmentioning
confidence: 59%
“…The fact that these findings were not absolute suggests that OCCs may adhere to both linear as well as nonlinear genetic models of progression . In the long term, it will be important to determine whether, the molecular pathways used for tumor growth and survival in these distinct regions move toward concordance, as is observed in other tumors …”
Section: Discussionmentioning
confidence: 99%